Time to Achieve Full Enteral Feeding in Very Low Birth Weight Infants and Associated Factors in Neonatology Unit - Sukmawati, Made; Kardana, I Made; Artana, I Wayan Dharma; Putra, Putu Junara; Cempaka, Putu Mas Vina Paramitha; Clearesta, Kartika Eda (Babali Publisher, 2023)
Background: Enteral intolerance in premature infants is associated with several morbidities, especially in very low birth weight (VLBW). There are only a few dietary practices to provide better outcomes in newborns with VLBW. This study aimed to assess the factors associated with the time to achieve full enteral feeding (FEF) in infants with VLBW. Methods: This was a retrospective study on infants with VLBW in the Neonatology Unit of Sanglah Central General Hospital, Bali from November 2020 to January 2022. The infants started trophic feeding with breastmilk and or formula milk. The age of FEF was determined when the target of 150 ml/kgBW/day was reached. The association of risk factors was analyzed using the Mann-Whitney test, the Kruskal-Wallis test, and linear regression analysis. Results: A total of 79 VLBW infants with a median gestational age of 30 weeks (25-38) were recruited. The median age of FEF was achieved in 9(7-15) days. Late trophic feeding (more than 24 hours), severe asphyxia, culture positive-sepsis, and using a mechanical ventilator were associated with a longer timing of FEF. While in the multivariate analysis, small for gestational age (SGA), late trophic feeding, severe asphyxia, absence of prenatal dexamethasone, and culture-positive sepsis were independent factors for longer FEF in this population. Conclusion: In VLBW infants, the age of FEF in our population was reached in 2 weeks. Small for gestational age, late trophic feeding, severe asphyxia, prenatal dexamethasone coverage, and culture-positive sepsis were associated with delay in FEF. Further studies of multi-centers and analyzing the factors of delayed TF might be needed.